Design and kinetostatic modeling of a compliant gripper for grasp and autonomous release of objects. (18th July 2018) - Ngo, Tien-Hoang; Tran, Hong-Van; Nguyen, Thang-An; Dao, Thanh-Phong; Wang, Dung-An
ABSTRACT: A gripper with an embedded compliant bistable mechanism (BM) for gripping and autonomous release of objects is developed. Due to adhesion forces, objects might stick to the end effector of a gripper upon release, where a shaking operation may be employed to release the objects. Vibration of the end effector induced by an impact pestle adjacent to the shuttle mass of the BM may achieve autonomous release of objects adhered to the end effector. Gripping and autonomous release of objects are accomplished when the BM moves between its two stable equilibrium positions. An analytical model is developed to predict the kinetostatic behavior of the BM and to assist in the design of the gripper. GRAPHICAL ABSTRACT: